Long-term outcomes of aortic valve insufficiency in patients with Takayasu arteritis - Yağmur, Feyyaz Hazar; Kutu, Muhammet Emin; Tastekin, Fatih; Avcu, Aysegul; Şan, Senar; Ocak, Tuğba; Yıldırım, Fatih; Kocaayan, Hasan; Bakkal, Safiye; Işık, Sema; Uludoğan, Burcu Ceren; Köroğlu, Semiha; et al. (Frontiers in Immunology, 2025)
ObjectiveTakayasu arteritis (TAK) is a rare vasculitis predominantly affecting the aorta and its branches. Aortic valve (AV) insufficiency is a clinically significant but underexplored manifestation of TAK. This study aimed to evaluate the prevalence, associated risk factors, and prognostic implications of AV insufficiency in a large, multicenter cohort of TAK patients.MethodsWe retrospectively analyzed data from 252 patients diagnosed with TAK across 11 rheumatology centers in Türkiye. Echocardiographic findings, clinical characteristics, treatment data, and long-term outcomes were collected. Severity and progression of AV insufficiency were assessed using standardized echocardiographic criteria.ResultsAV insufficiency was present in 33% of patients, with moderate to severe forms observed in 12% and with 7% requiring valve replacement. Ascending aorta and renal artery involvement, hypertension, and heart failure were more frequent in patients with AV insufficiency. Over a median follow-up of 97 months, AV insufficiency progressed in 17% of baseline affected patients. The absence of subclavian artery involvement and vascular damage index (VDI) were found to be independent risk factors for AV insufficiency progression. Despite the structural progression, AV insufficiency did not significantly impact mortality, relapse rates, vascular damage index, or treatment patterns.ConclusionAV insufficiency is the most clinically relevant valvular pathology in TAK, and its baseline presence did not adversely influence TAK disease outcomes. Progression was observed in a subset of patients, and this was associated with higher VDI scores, particularly among those without subclavian artery involvement. Timely diagnosis and multidisciplinary management may mitigate its impact on long-term outcomes.